Pengembangan Modul Desain Didaktis Materi Statistika pada Pembelajaran Matematika di kelas VIII - Islamiyah, Tsuwaibatul; Mahmudah, Wilda (UJMC (Unisda Journal of Mathematics and Computer Science), 2024)
This research aims to develop a didactical design module for statistical material that is valid, practical, and effective. The type of research used is R&D (Research and Development) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The instruments used are questionnaires regarding students' initial needs, teacher interview sheets, validation sheets, student response questionnaires, and learning outcomes tests. The results of the research show that the didactic design module for statistical material is valid in terms of material validity, obtaining an average score of 4.22 with "very good" criteria, and in terms of media validity, it obtained an average of 4.54 with "very good" criteria. The didactic design module developed was also stated to be practical in that students' responses obtained an average score of 4.8 with the criteria "very good". This module is also effective because a completion score percentage of 96% is obtained with very effective criteria.